The emergence of the DMO concept in Japan: Confusion, contestation and acceptance. (September 2018) - Nagai, Hayato; Doering, Adam; Yashima, Yuji
Abstract: Destination marketing and/or management organizations (DMOs) have been acknowledged as an essential component of the tourism system. However, the ability of DMOs to manage and coordinate destination development in contemporary society is now being questioned by scholars. The focus of this regional spotlight is Japan, a country that has recently turned to tourism as the tool to facilitate economic growth. The paper examines the early emergence of the registered DMO program introduced by the Japanese government in 2015, with a particular focus on how the concept of DMO is being adopted and understood by tourism practitioners at local tourism destinations across the country. Offering insights into the ways the concept of DMO is understood, experienced and employed in Japan, a non-Western context, the paper contributes to the international debate concerning the future role of DMOs globally. Highlights: Provides an overview of the new registered DMO program in Japan. Explores how the concept of DMO is viewed and understood by tourism practitioners. Contributes to the international debate concerning the future role of DMOs.